Efektivitas Terapi Psikoedukasi dan Terapi Murattal Terhadap Kecemasan Pasien Preoperasi Fraktur di Ruang Perawatan Bedah Rsud Raden Mattaher Jambi - Diah Merdekawati; Sagiran Sagiran; Azizah Khoiriyati (IJNP (Indonesian Journal of Nursing Practices), 2016)
Fracture is a break of continuity of bone and cartilage tissue caused by injury or trauma. Fracture treatments are konservasif and operating based on the severity of fracture and mental attitude of the patient. Fracture patients who underwent surgery at the Raden Mattaher Jambi Hospital in 2012 (January-October) is 157, 36 patients get delay surgery becaused increase in blood pressure, pulse and body temperature is always changing as a result of anxiety. Therapy can be used to reduce the anxiety are psychoeducation and murattal. This research is a quasi-experiment with form nonequivalent control group design that aims to analyzing the effectiveness of psychoeducation and murattal therapy on anxiety of preoperative fracture patient in Ruang Perawatan Bedah Raden Mattaher Jambi Hospital 2013. Sample as many as 35 respondents. The research instrument was Rate Hamilton Anxiety Scale (HARS) and using statistical tests Repeated Anova. This research shows that a decline in the level of anxiety before and after the intervention given that the biggest difference is the respondent given murattal therapy, the difference was found in 3 interventions measures through. Comparison of anxiety of preoperative fracture patients with murattal therapy and interventions to a room have a large difference. Murattal therapy can be used to decline the anxiety of preoperative fracture patient in Raden Mattaher Jambi Hospital. The next research can analyze about physiology symptom and factors that cause anxiety. Keywords: Anxiety, Fracture, Psychoeducation and Murattal